Study of Hydroxyapatite from White Mussel Shells Using Nitric Acid Solvent with the Sol-Gel Method - Alia Febrianti Muliina; Nana Roudlotul Fitri; Suprihatin Suprihatin (Universitas Islam Raden Rahmat, Malang, 2025)
Mussel shells contain high calcium levels, making them suitable for hydroxyapatite (HAp) synthesis. HAp is a bioceramic widely applied in bone implant materials. This study synthesized HAp from white mussel shells (Corbula faba Hinds) using nitric acid via the sol-gel method. The effects of pH (8–12) and stirring temperature (30°C–90°C) on product yield and crystallinity were evaluated. X-ray fluorescence (XRF) was used to analyze elemental composition, while X-ray diffraction (XRD) characterized the crystalline phase. Results showed that increasing pH and temperature generally enhanced both yield and crystallinity. Optimal conditions were observed at pH 10 and higher temperatures, demonstrating the effective conversion of mussel shells into hydroxyapatite. These findings support the potential of marine biowaste as a sustainable raw material for biomedical applications.